Efek latihan kesamaptaan terhadap kadar D-Dimer pada anggota militer Kodam I Bukit Barisan - R. Prathama Wiradharma; Nizam Zikri Akbar; Adi Koesoema Aman (Intisari Sains Medis, 2019)
Background: Several reports and experiences show that when doing heavy exercise often occur complaints which direct the diagnosis towards Venous Thrombo-Embolism (VTE) in the form of painful and swollen feet. This was due to hypercoagulation and resulted in VTE. The D-dimer level is a measure of clot formation and lysis resulting from the breakdown of fibrinogen and fibrin during fibrinolysis. Therefore this study aimed to see an increase in D-Dimer which is a marker of increased fibrinolysis.Method: This study took a sample of blood from 30 soldiers who were declared healthy. The sample was checked for D-Dimer 1 hour before and after the test. The physical readiness test is a standard for assessing the readiness of soldiers in carrying out tasks. The sample was evaluated whether there was an increase after the test. Examination using Coatron machine with the Immuno Turbidimetric Assay method.Result: 30 people are men with an average age of 19-22 years. D-Dimer showed a significant difference with a mean of 92.83 Â± 49.62 SD before the test and after the test found a mean of 127.53 Â± 57.75 SD with p = 0.001 (p <0.05).Conclusion: The increase in D-Dimer shows an increase in blood coagulation processes and fibrinolysis and can occur in individuals who often carry out heavy activities. D-Dimer and Dopler ultrasound screening should be carried out on a periodic check before carrying out the physical readiness test.